With a beginning? Or eternal? Origins and controversies in cosmology in the middle of the last century - Videira, Antônio Augusto Passos; Vieira, Cássio Leite (Cadernos de Astronomia, 2023)
A few years after the end of World War II, cosmology - a discipline then in search of respectability - was involved in a controversy regarding the question of whether (or not) the universe had an origin. In this article, we review that period, describing the main ideas and names of this unique event.